TERRITORIAL INTEGRITY AND CONSENT IN THE CHAGOS ADVISORY OPINION. Issue 1 (January 2020) - McCorquodale, Robert; Robinson, Jennifer; Peart, Nicola
Abstract: A key element of the right to self-determination is territorial integrity. This has usually been considered solely in relation to the territorial integrity of an existing State seeking to resist claims by peoples for the right to self-determination. Yet the Chagos Opinion by the International Court of Justice examines a different type of territorial integrity—that of the colonial territory itself. This article explores the consequence of the Court's view that the territorial integrity of the colonial territory is a matter of customary international law, and that any division, integration or other disruption of that colonial territory after December 1960 is unlawful, without the free and genuine consent of the people of the colonial territory. In particular this article seeks to explore what the Chagos Opinion means in terms of the territorial integrity of a colonial territory. It also examines the required conditions for ascertaining a free and genuine consent of the people of that territory, and the legal effects of not complying with them. There is also consideration of the implications for other situations from the clarification of customary international law in the Chagos Opinion, with a special focus on West Papua.